Thinness, overweight, and obesity in indigenous school children and youth in Mexico - Bert B. Little; Robert M. Malina; Maria Eugenia Pena-Reyes; Guilermo Bali Chavez (Annals of Human Biology, 2019)
Background: The prevalence of overweight (OWT) and obesity (OB), defined by the body mass index (BMI, kg/m2) among children and youth has increased worldwide in the last 30–40 years. Aim: To evaluate the weight status, defined by the BMI, of indigenous school children and youth resident in different regions of Mexico Subjects and methods: Students 6–18 years (31,448 boys, 27,306 girls) were enrolled in bilingual schools for indigenous children and youth in Mexico in 2012. Height and weight were measured; the BMI was calculated. The BMI of each student was classified relative to International Obesity Task Force (IOTF) age- and sex-specific criteria as thin (three grades), normal, overweight (OWT) or obese (OB). The sample was divided into five geographic regions for analysis: North, Central, South-Gulf, South-Pacific, and South-Southeast. Age- and sex-specific prevalence, 95% confidence intervals, and Chi-square tests were calculated. Results: Prevalence of OWT + OB was highest in the South-Gulf, South-Pacific and South-Southeast regions and lowest in the North and Central regions, while thinness was most prevalent in the North and Central regions. Conclusion: Prevalence of severe and moderate thinness was relatively low, while the combined prevalence of OWT + OB was generally more prevalent in indigenous boys than girls. However, the prevalence of thinness, OWT + OB among indigenous children and youth was lower than in the general population of children and youth in Mexico.